Discipline and Punishment in Global Politics - Leatherman, J. author. aut Link
XIX, 240 p.
Keywords: Global politics is a crowded stage of players competing for power and authority. Who is in charge of what? How do they stay in charge and what are the effects? This volume raises these questions in case studies on regimes of torture and surveillance in women's rights, border control, media, global capital and religion.